Does Village Deliberation Forum Affect on The Quality of Road Infrastructure Inter-Village? - Fery Tri Setyawan; Vid Adrison (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2020)
Decentralization is expected to improve the provision of public infrastructure by bringing local government closer and more responsive to the community needs. However, based on the theory, decentralization can lead to principal agent problems due to the presence of asymmetric information. Local government potentially want to prioritize their needs more than the needs of the resident. One proposed scheme to mitigate this problem is through participatory government. This study attempts to estimate the impact of decentralization on the provision of the public infrastructure, especially community participation through village deliberation forum on the provision of inter-village road infrastructure in Indonesia. Using a logit estimation approach, this study analyzes the impact of implementing village deliberation forum on the quality of inter-village roads in Indonesia in 2018. The estimation results show that the implementation of village deliberation forum has a positive effect on the probability that the village have good road quality. Thus, this study supports previous researches on the positive impact of public participation on the quality of public infrastructure.